The Influence of Leadership Style, Training and Competence on Non-ASN Employee Engagement Through Work Discipline as a Mediating Variable in the Housing and Residential Areas Service of Binjai City - Ade Febri Pratiwi; Muhammad Chaerul Rizky; Darmilisani Darmilisani (Journal of Research in Social Science and Humanities, 2025)
Using work discipline as a mediating variable, this study investigates how competency, training, and leadership style affect employee engagement at Dinas Perumahan dan Kawasan Permukiman Kota Binjai. PLS-SEM, or partial least squares structural equation modeling, was the quantitative method employed in the study. Non-civil servant (non-ASN) employees who actively participate in the day-to-day activities of the department were among the respondents. According to the study, employee engagement was significantly impacted by competency, training, and leadership style. The relationship between these three distinct elements and employee engagement is strengthened by work discipline, which serves as a mediator. These findings suggest that improving employee engagement can be achieved through effective leadership, relevant training programs, enhanced employee competence, and the reinforcement of work discipline. The practical implication of this study is that organizations should implement integrated managerial strategies to create a productive, disciplined, and highly committed workforce